IEEE Visualization, 2002. VIS 2002.
DOI: 10.1109/visual.2002.1183754
|View full text |Cite
|
Sign up to set email alerts
|

CPR - curved planar reformation

Abstract: Visualization of tubular structures such as blood vessels is an important topic in medical imaging. One way to display tubular structures for diagnostic purposes is to generate longitudinal crosssections in order to show their lumen, wall, and surrounding tissue in a curved plane. This process is called Curved Planar Reformation (CPR). We present three different methods to generate CPR images. A tube-phantom was scanned with Computed Tomography (CT) to illustrate the properties of the different CPR methods. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
0

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 11 publications
0
114
0
Order By: Relevance
“…In a second step, curved planar reconstruction (CPR) [30] is used to create a panoramic view of the nerve along its centreline (see Figure 6 b). A first identification of the nerve's borders is automatically suggested to the user.…”
Section: Anatomical Structures Segmentationmentioning
confidence: 99%
“…In a second step, curved planar reconstruction (CPR) [30] is used to create a panoramic view of the nerve along its centreline (see Figure 6 b). A first identification of the nerve's borders is automatically suggested to the user.…”
Section: Anatomical Structures Segmentationmentioning
confidence: 99%
“…A native plane (a) cannot represent all structures of the placenta at once. Therefore, we use our segmentation method (b), correct the motion in this area using [3], project the placenta mask into the the resulting isotropically resolved volume (c), extract the mean curvature flow skeleton [10] (black lines in (d)), use the resulting points to support a curved surface plane (e) and visualize this plane with curved planar reformation [5] (f). The plane in (f) covers only relevant areas, hence gray value mapping can be adjusted automatically to emphasis placental structures.…”
Section: Resultsmentioning
confidence: 99%
“…It is supported by a mean-curvature flow skeleton [10] generated from the triangulated polygonal mesh of the placenta segmentation and textured similar to curved planar reformation [5], see Figure 3. Although this part is not evaluated thoroughly, clinicians revealed that such a representation is potentially desirable since it compares well to a flattened placenta after birth.…”
Section: One Input Stackmentioning
confidence: 99%
“…21 The vertebral region is then segmented around the spinal canal using a vertebral template consisting of substructures of vertebral body, transverse processes, and a spinous process. 20 To partition the spine column into vertebrae, curved planar reformations (CPR) 22 in both sagittal and coronal directions are computed along the centerline of the spinal canal. Aggregated intensity profiles (AIP) along the normal direction of the projected centerline on the sagittal and coronal CPR are computed, and dynamic programming is performed to locate the vertebral disks that correspond to valleys in the AIP.…”
Section: Spine Segmentation and Partitioningmentioning
confidence: 99%